Macrocyclic Hamilton-type receptors comprising a ferrocene pivot. Issue 10 (3rd October 2018) - Pisciottani, Luca; Douarre, Maxime; Bibal, Brigitte; Davies, Clotilde; Roberts, Holly; Kauffmann, Brice; Horswell, Sarah L.; Tucker, James H. R.; McClenaghan, Nathan D.
Abstract: Synthetic hydrogen-bonding receptors are described, which incorporate a central electroactive ferrocene moiety grafted with two adjacent bis(amido)pyridine motifs and an aliphatic tether (14 and 18 methylene units for1 and2, respectively) completing the macrocycle. The crystallographic structure, barbiturate guest-binding studies and electrochemical data are provided for the more strongly-binding macrocycle2 . Abstract :